Do gender stereotypes bias the processing of morphological innovations? The case of gender-inclusive language in Spanish - Stetie Noelia Ayelén; Zunino Gabriela Mariel (Psychology of Language and Communication)
Classical grammatical studies in Spanish only consider binary gender and claim that gender assignment is an arbitrary process. However, psycholinguistic evidence suggests that gender morphology, lexical semantics, and gender stereotypes condition language processing. Recently, gender-inclusive language proposals have proliferated in several languages, and in Spanish, the use of the nonbinary morphological variant [-e] has spread considerably. This article presents the results of a self-paced reading task that evaluated the influence of gender stereotypes (role names with semantic male or female bias) on the processing of this morphological innovation. There was a semantic bias effect in the first spillover word, but there were no statistically significant differences for noun phrase, wrap-up region, and total sentence reading times. The results showed that gender stereotype effect occurs relatively early and at the local level. Moreover, nonbinary morphological innovations may be specializing in the representation of mixed groups of people.